1978
DOI: 10.1259/0007-1285-51-605-351
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal post-mortem radiography—experience with 2500 cases

Abstract: A review of 2500 routine post-mortem radiographic examinations of perinates is presented. It is concluded that the procedure is of value in the detection of abnormalities which may have contributed to the death of the perinate and which may have escaped detection at autopsy. The use of contrast agents may assist in the evaluation of congenital abnormalities, especially of the cardiovascular system. Post-mortem radiographic examination may be especially helpful in the evaluation of perinates for whom permission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 11 publications
1
23
0
2
Order By: Relevance
“…As antenatal diagnostic ultrasound continues to improve [23], with a low incidence and prevalence of skeletal dysplasias and other fetal bony abnormalities, and most significant abnormalities now being identified antenatally (and typically the indication for termination of pregnancy), the yield of routine PMSS examinations to provide significant additional information in apparently anatomically normal fetuses and stillbirths is low. However, from the published literature, it is difficult to evaluate the additional value of PMSS over autopsy, or vice versa, partly because of methodological difficulties or selection criteria in the populations studied, although several studies have examined this issue since the 1970s [24][25][26][27][28][29][30][31].…”
Section: Routine or Targeted Pmss?mentioning
confidence: 99%
See 1 more Smart Citation
“…As antenatal diagnostic ultrasound continues to improve [23], with a low incidence and prevalence of skeletal dysplasias and other fetal bony abnormalities, and most significant abnormalities now being identified antenatally (and typically the indication for termination of pregnancy), the yield of routine PMSS examinations to provide significant additional information in apparently anatomically normal fetuses and stillbirths is low. However, from the published literature, it is difficult to evaluate the additional value of PMSS over autopsy, or vice versa, partly because of methodological difficulties or selection criteria in the populations studied, although several studies have examined this issue since the 1970s [24][25][26][27][28][29][30][31].…”
Section: Routine or Targeted Pmss?mentioning
confidence: 99%
“…Reviews of between 100 and 2500 stillbirths and perinatal death radiographs from the 1970s and 1980s suggested that routine radiography was diagnostic in 13.5%, gave additional value in 34.5%, and of no diagnostic value in 52% [24][25][26][27], with authors concluding that "… a radiological examination should not be routinely performed, … but should be considered in the presence of dwarfism, or other limb abnormalities and when the gestational age is uncertain" [25]. Another study of over 500 perinatal deaths In some skeletal dysplasias such as achondrogenesis type 2, there is absent or severely impaired vertebral body ossification (a), which may be superficially similar to a normal fetus of 10-11 weeks gestation (b).…”
Section: Routine or Targeted Pmss?mentioning
confidence: 99%
“…12 15 19 24-26 Although it is time consuming and presents challenges in execution and interpretation (and because of this is perhaps underused), it should be considered when full autopsy is declined and malformation is suspected, particularly when other imaging modalities such as MRI are not available.…”
Section: Contrast Radiographymentioning
confidence: 99%
“…The largest experience with 2,500 cases has been reported by Foot [6] from New Zealand. The incidence of bone dysplasia is 1% but the perinatal post partum radiography was of value for detection of conditions which may be responsible for the death of the infants, especially pneumothorax, pneumopericardium.…”
Section: D) Overall Diagnosismentioning
confidence: 99%